Scientific and theoretical foundations for the use of skipping in the physical education of high school students - Andriushchenko , Tetiana; Moskalenko , Nataliia; Mykytchyk , Olha; Lavrova , Larysa; Savchenko , Viktoriia (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. In the work presents the justification and verification of the effectiveness of organizational and methodical conditions for the use of skipping means in the physical education of high school students to improve their physical condition. Currently, one of the most pressing problems today is improving the physical condition of high school students. According to T.Yu. Krutsevich, N.E. Pangelova, N.V. Moskalenko, O.V. Andreeva and co-authors, the school does not fully solve the problems of meeting children’s biological need for physical activity. The purpose of to scientifically substantiate the organizational and methodological conditions for using skipping means at the lessons with students of 10-11 grades of general secondary educational institutions to improve their physical state. Research methods: analysis of scientific and methodological literature, questionnaires, anthropometric research methods, pedagogical testing, method of indices according to the methodology of T.Yu. Krutsevich, express assessment of physical health according to the method of G.L. Apanasenko, pedagogical experiment, methods of mathematical statistics. Results. Presents the results of the ascertainment stage of the pedagogical experiment, which consisted in determining the indicators of the physical condition of high school students and the main motives of students for physical education and sports. Developed a program of skipping classes for students of 10-11 grades, which was implemented during the third quarter of academic year in physical education lessons. Skipping means were also used during the academic year in physical education lessons in the variable modules “Track and Field”, “Football” in the first and fourth quarters, “Volleyball” in the second quarter. The structural elements of the program are: purpose, tasks, principles, content, methods and criteria for the effectiveness of using skipping means in the process of physical education of high school students. The effectiveness of the skipping program has been proven experimentally. In the students of the experimental groups, a significant improvement in morphofunctional indicators (CC, heart rate, VC, Stange test, Gench test, physical work capacity) was determined. A significant improvement was determined by the results of physical fitness testing in terms of endurance, speed, strength, speed-power abilities, dexterity, and flexibility. The quality of performance of the students of the experimental groups of the «Jumping rope» test has significantly increased. In indicators of physical health, there was a significant increase in the average number of points in the overall assessment, the number of schoolchildren with a low level of physical health also decreased, and the number of students with average, above average and high levels increased. Conclusions. The results of the research made it possible to scientifically substantiate the organizational and methodological conditions for the implementation of the program of skipping classes in the process of physical education of high school students, which contain four blocks: organizational, diagnostic, programmatic and control.